African Healing, Sacrifice, Number Symbolism, and the Psychology of C. G. Jung. (2nd January 2017) - Radomsky, Lynne
Abstract : The idea of animal sacrifice and of indigenous healing practices presents a challenge to Western-based predilections on many levels. For the African healer, the honoring of the sacrifice in its essence is directly related to the healing energy. This article provides both a phenomenological and an analytical portal into African healing practices. It begins with a descriptive narrative of the author's experience of the "other" in the liminal space of ritual taking place in a rural South African township. The analytical sections focus on the psychology of C. G. Jung and the amplification of number symbolism in relation to the initiatory ceremonies of the African indigenous healer in which animal sacrifice is central. The author has nurtured a deep and intimate collaboration with various indigenous healers in South and Southern Africa for many years. By sharing an aspect of the rich archetypal world of the African healer, the author hopes to encourage a deeper understanding of these numinous practices and a respect for the differentiated consciousness of the African psyche.